2014
DOI: 10.1111/trf.12928
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte collection using a novel apheresis system eases the procedure and provides concentrates of high quality

Abstract: GC with the fully automated Optia device is safe for donors, is not inferior to its forerunner Cobe Spectra, produces GTX of a high quality, and requires less manpower than the Cobe Spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The CD34-positive cell collection efficiency of Spectra Optia was found to be comparable to or better than that of COBE Spectra [24][25][26][27]. GC efficiency has also been compared between COBE Spectra and Spectra Optia systems [7,28]. However, in these studies HES was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD34-positive cell collection efficiency of Spectra Optia was found to be comparable to or better than that of COBE Spectra [24][25][26][27]. GC efficiency has also been compared between COBE Spectra and Spectra Optia systems [7,28]. However, in these studies HES was used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HES is not available in some countries, and it is not approved as a drug in Japan. A cell separator system, Spectra Optia, which is the successor of COBE Spectra, has been reported to increase the yield of granulocyte collection (GC) [6,7]. In these studies, HES was used during GC.…”
Section: Introductionmentioning
confidence: 99%
“…The target process volume of whole blood was set at 7 L; however, the collections were completed when 500 ml of HES was consumed in the HES group. The PMN collection program of Optia has an automated interface monitoring system placed in the chamber, which performs real‐time interface monitoring, interpretation, and adjustment for flexible procedural control 18 . However, collection preference needs to be optimised in the non‐HES group because the clear interface is not formed in the absence of HES.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several studies have shown that a novel cell separator (Spectra Optia) could provide greater granulocyte yields than an earlier system (COBE Spectra), which was used in our previous study 18,19 . We hypothesized that the use of a newer device would spare the need for using HES.…”
Section: Introductionmentioning
confidence: 93%
“…The Optia device has also been used to collect granulocytes from healthy blood donors and family donors mobilized with prednisolone or G-CSF. [ 29 ]. One study showed that the Optia ® device is not inferior to the COBE Spectra forerunner and produces high-quality granulocyte concentrates with greater absolute neutrophil yields.…”
Section: Granulocyte Collection and Storagementioning
confidence: 99%